PUBLIC EXTERNAL DEBT AND MACROECONOMIC STABILITY IN UZBEKISTAN: A REVIEW AND DESCRIPTIVE ANALYSIS - Elmirzayev Diyorbek Shoniyoz o’g’li (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract: This article examines the evolution of public external debt in the Republic of Uzbekistan from 2015 to 2024, analyzing its pivotal role in the country’s transition from an autarkic, state-led model to an open market economy. The study posits that while the nominal stock of public debt surged following the 2017 exchange rate liberalization and subsequent investment boom, the debt-to-GDP ratio has stabilized within sustainable thresholds due to robust nominal GDP growth and prudent fiscal management (IMF, 2025). Through a descriptive analysis of the evolving institutional framework, the research highlights the significance of the 2023 Law on State Debt and the maintenance of substantial international reserves in mitigating solvency risks (Ministry of Justice, 2023). However, the analysis also identifies persistent structural vulnerabilities, specifically the high degree of foreign currency denomination and contingent liabilities arising from State-Owned Enterprises (SOEs). Ultimately, the research concludes that public debt served as a critical macroeconomic stabilizer during external shocks, positioning Uzbekistan for a phase of fiscal consolidation and deeper domestic market development.